The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21037/qims-20-546
|View full text |Cite
|
Sign up to set email alerts
|

CT-derived pulmonary vascular metrics and clinical outcome in COVID-19 patients

Abstract: To assess pulmonary vascular metrics on chest CT of COVID-19 patients, and their correlation with pneumonia extent (PnE) and outcome, we analyzed COVID-19 patients with an available previous chest CT, excluding those performed for cardiovascular disease. From February 21 to March 21, 2020, of 672 suspected COVID-19 patients from two centers who underwent CT, 45 RT-PCR-positives (28 males, median age 75, IQR 66-81 years) with previous CTs performed a median 36 months before (IQR 12-72 months) were included. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 30 publications
5
46
0
Order By: Relevance
“…This possibly justifies the observed association between more extensive lung involvement and elevated PA/A ratio in our study. In line with our results, Spagnolo et al also showed that PA/A ratio significantly increased subsequent to COVID-19 infection and was significantly correlated with the extent of pneumonia (26).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This possibly justifies the observed association between more extensive lung involvement and elevated PA/A ratio in our study. In line with our results, Spagnolo et al also showed that PA/A ratio significantly increased subsequent to COVID-19 infection and was significantly correlated with the extent of pneumonia (26).…”
Section: Discussionsupporting
confidence: 93%
“…In line with our results, Spagnolo et al. also showed that PA/A ratio significantly increased subsequent to COVID-19 infection and was significantly correlated with the extent of pneumonia ( 26 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The weak nature of these correlations could be explained first by considering that a large number of pre-existing factors and frailties such as comorbidities, weight, muscle mass, and age, strongly interplay between pneumonia extent and clinical and laboratory parameters of patients with COVID-19 needing hospitalisation [ 32 ]. Moreover, the increasingly demonstrated impact of pulmonary arterial thrombosis, which has shown little to none correlation with pneumonia extent [ 33 ] and can occur in lung parenchymal areas unaffected by pneumonia [ 34 37 ], represents a sizeable contribution to the mismatch between clinical parameters and pneumonia extent.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, considering the actual prevalence of pulmonary thromboembolism in our small cohort of COVID-19 patients with moderate to high risk according to the Wells Score and D-dimer values, we found a two-to fivefold increase to the prevalence reported by the original study by Wells et al 11 These data support the hypothesis that sees COVID-19 patients having an increased thromboembolic risk that tends to manifest itself as pulmonary arterial thrombosis and non-pulmonary thromboembolism even in patients under thromboembolic prophylaxis with anticoagulant therapy, in the association of global inflammation-induced thrombophilia and direct pulmonary vascular damage. 7,15 This scenario also possibly indicates that the sensitivity of conventional diagnostic criteria could be insufficient to correctly diagnose pulmonary thromboembolism in COVID-19 patients. 10 Limitations of this work include its monocentric and crosssectional nature: the quite short period elapsed from the outbreak of COVID-19 in our area and the still-ongoing emergency hindered the possibility to obtain full clinical and anamnestic data, long-term prognostic information, as well as to fully exclude a selection bias linked to the eventuality that some patients complying our inclusion criteria were not referred for CTPA, because they had contraindications to the administration of iodinated contrast agents or because CT examinations were temporarily unavailable due to the unprecedented number of patients needing unenhanced chest CT for triaging purposes.…”
Section: Discussionmentioning
confidence: 99%